2014
DOI: 10.1063/1.4886961
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Rabi oscillations in a non-polar InGaN quantum dot

Abstract: Experimental observation of Rabi rotations between an exciton excited state and the crystal ground state in a single non-polar InGaN quantum dot are presented. The exciton excited state energy is determined by photoluminescence excitation spectroscopy using two-photon excitation from a pulsed laser. The population of the exciton excited state is seen to undergo power dependent damped Rabi oscillations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 29 publications
(21 reference statements)
0
21
0
Order By: Relevance
“…All calculations were performed on a 50 × 50 × 30-nm 3 supercell with periodic boundary conditions. With these assumptions, the calculated ground state transition energies were in the range of 2.7 to 2.9 eV, close to typical experimental values [27,32,33,[41][42][43][44] and those discussed below. Therefore, the chosen geometries and indium contents should give a reasonable description of the structures considered here.…”
Section: Theoretical Calculations Of Dolpmentioning
confidence: 53%
“…All calculations were performed on a 50 × 50 × 30-nm 3 supercell with periodic boundary conditions. With these assumptions, the calculated ground state transition energies were in the range of 2.7 to 2.9 eV, close to typical experimental values [27,32,33,[41][42][43][44] and those discussed below. Therefore, the chosen geometries and indium contents should give a reasonable description of the structures considered here.…”
Section: Theoretical Calculations Of Dolpmentioning
confidence: 53%
“…III-nitride materials have not only achieved commercial success in the realization of highly efficient photonic devices including light emitting diodes (LEDs)4 and lasers5, but also exhibit particular advantages for the development of quantum light sources6, and the exploration of quantum information science789 and light-matter interactions210. However, in the context of both LEDs and quantum light sources, the conventional polar nitrides exhibit limitations due to the large polarization-induced internal electric fields arising in heterostructures which reduce the spatial overlap of the electron/hole wavefunctions.…”
mentioning
confidence: 99%
“…7 Previous work by Zhu et al 8 has demonstrated the growth of non-polar a-plane InGaN QDs by the modified droplet epitaxy (MDE) method with exciton lifetimes an order of magnitude smaller than comparable polar QDs, 9 and which exhibit improved temperature stability 10 and Rabi oscillations. 11 However, the photoluminescence (PL) linewidth of the QDs grown by MDE remains typically in excess of 1 meV. It is not clear whether this is a measure of the true linewidth of the emission, or whether the measurement is affected by spectral diffusion.…”
mentioning
confidence: 99%
“…It is not clear whether this is a measure of the true linewidth of the emission, or whether the measurement is affected by spectral diffusion. In this letter, an alternative method for the growth of non-polar (11)(12)(13)(14)(15)(16)(17)(18)(19)(20) InGaN QDs by metal organic vapour phase epitaxy (MOVPE) is reported, utilising a temperature ramp in an ammonia and nitrogen environment to achieve improved luminescence properties. Low temperature cathodoluminescence (CL) and micro-photoluminescence (µPL) show the presence of sharp peaks in the collected spectra, whose linewidth is limited by the resolution of the detection system.…”
mentioning
confidence: 99%
See 1 more Smart Citation